2011
DOI: 10.1111/j.1365-3040.2011.02396.x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of barley root and shoot proteomes to long‐term nitrogen deficiency, short‐term nitrogen starvation and ammonium

Abstract: Cereals are major crops worldwide, and improvement of their nitrogen use efficiency is a crucial challenge. In this study proteins responding to N supply in barley roots and shoots were analysed using a proteomics approach, to provide insight into mechanisms of N uptake and assimila-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(57 citation statements)
references
References 75 publications
(156 reference statements)
1
53
0
3
Order By: Relevance
“…Glutamine synthetase (GS) is an enzyme that plays an essential role in N metabolism by catalyzing the ATP‐dependent conversion of glutamate and ammonia to form glutamine. Previous studies have showed that N and P deficiencies cause a decrease in the abundance of GS in barley and maize . In this study, the abundances of both GS1 and GS2 were down‐regulated in N‐ and P‐deficient females but not in males, suggesting that long‐term N and P deficiencies may affect nitrogen assimilation more in females than in males.…”
Section: Discussionmentioning
confidence: 42%
“…Glutamine synthetase (GS) is an enzyme that plays an essential role in N metabolism by catalyzing the ATP‐dependent conversion of glutamate and ammonia to form glutamine. Previous studies have showed that N and P deficiencies cause a decrease in the abundance of GS in barley and maize . In this study, the abundances of both GS1 and GS2 were down‐regulated in N‐ and P‐deficient females but not in males, suggesting that long‐term N and P deficiencies may affect nitrogen assimilation more in females than in males.…”
Section: Discussionmentioning
confidence: 42%
“…An increase and decrease in chloroplast RNA binding protein was observed in salt-tolerant and salt-sensitive barley genotypes, respectively (Fatehi et al 2012a). Two chloroplast RNA-binding proteins, Cp31AHv and Cp31BHv, increased in abundance, and one of these (Cp31BHv) also increased under long-term nitrogen deficiency in salt-tolerant H. vulgare L. cultivar (Møller et al 2011).…”
Section: Protein Translation and Processingmentioning
confidence: 95%
“…From a physiological perspective, nitrate nutrition is associated with elevated cytokinin biosynthesis, increased organic acid content, and soil alkalinization, while ammonium nutrition is associated with increased activity of alternative respiratory pathways, elevated amino acid content, and soil acidification (Walch-Liu et al, 2005;Patterson et al, 2010). In addition, recent studies have demonstrated distinct transcriptome, proteome, and protein phosphorylation signatures in plants supplied with either ammonium or nitrate as a nitrogen source (Patterson et al, 2010;Møller et al, 2011;Engelsberger and Schulze, 2012).…”
mentioning
confidence: 99%